Aminocyclopyrachlor: New Option for Trumpet Flower Control in Pastures - REIS,F.C. (2016)
ABSTRACT The species Tecoma stans, introduced to Brazil to be cultivated in urban centers as street trees, in parks and gardens, became important pasture weed. The mechanical control of this species is difficult because the plant presents a large number of sprouts when are mowed. Furthermore, the herbicides usually used in pasture have been shown to be inefficient to control it. This research evaluated the trumpet flower control effectiveness using a new herbicide (aminocyclopyrachlor) applied alone in increasing doses to the cut stump for the control of resprouts and mixed with metsulfuron-methyl in applications to intact plant leaves. The experiment with foliar applications used increasing doses of herbicides (aminocyclopyrachlor + metsulfuron-methyl). Applications of only aminocyclopyrachlor to the cut stump and foliar application of a herbicidal mixture (aminocyclopyrachlor + metsulfuron-methyl) were effective in the control of trumpet flower.